Elite Sectarianism, Foreign Intervention, and Political Change - Awad, Ramzi (2023)
Since its conception and until 2020, Lebanon has been riddled by a plethora of political crises, from gridlocks, economic crises, and many more institutional failures to all-out war. Despite all, the Lebanese “formula” has been persistent throughout time. Arguably, this formula of power sharing and its subsequent relation to foreign intervention started long before the formation of the modern Lebanese state and can be traced to The Reglement Organique at the times of the Ottoman Empire. However one may see it, group dynamics along sectarian lines have long existed in the public sphere of the now-modern Lebanese state and have intensified Post-Arab Spring. Surprisingly, with this system’s history of shortcomings, systemic change is yet to be achieved. Throughout its history, politics in Lebanon is synonymous with Elite politics, regional and international influence, and violence. This medley of factors has contributed to the system’s impermeability to democratic political change.